A meta-analysis of the effects of resistance training on blood sugar and pregnancy outcomes. (December 2020) - Yaping, Xie; Huifen, Zhao; Chunhong, Liu; Fengfeng, Huang; Huibin, Huang; Meijing, Zhao
Highlights: This study shows that resistance training can improve blood sugar levels in patients with GDM, including their fasting and average 2-h post-meal blood glucose levels. This study shows that resistance training can improve insulin dosage and rate of insulin injection in patients with GDM. This study shows that resistance training can reduce the incidence of macrosomia in patients with GDM. Although there are not many studies on resistance training and only a few are included in this meta-analysis, the results show that resistance training is worthy of clinical promotion. Abstract: Problem: There are different conclusions about the effects of resistance training on blood sugar levels and pregnancy outcomes in gestational diabetes mellitus (GDM) patients. Background: Resistance training is recommended as an easier and more practical method to exercise for women with GDM due to their growing belly. Although some researchers have explored this notion, there are no consistent conclusions about its effects. Aim: To explore whether resistance training has an effect on blood sugar levels and pregnancy outcomes in patients with GDM in randomized controlled trials. Method: Pubmed, Cochrane Library, CINAHL, Embase, Scopus, Web of Science, Clinical Trials, CKNI, Wanfang Database, VIP Database, and Chinese Biomedical Literature Database were systematically searched since their establishment to April 2019. Relevant meta-analyses, reviews, and eligible literature were also searched. The quality of the included literature was evaluated according to the Cochrane Assessment Manual 5.1.0. Meta-analysis was performed using Revman 5.3 software. Findings: A total of four studies ( n = 242 patients) were included. Compared to the control group, there were statistical differences in fasting blood glucose level [MD=-0.37, 95%CI=(-0.65, -0.09), Z = 2.62, P = 0.009], average 2-h post-meal blood glucose level [MD=-0.96, 95%CI=(-1.80, -0.12), Z = 2.25, P = 0.02], insulin dosage [MD=-0.58, 95%CI=(-0.99, -0.17), Z = 2.75, P = 0.006], rate of insulin injection [RR=0.52, 95%CI=(0.31, 0.86), Z = 2.54, P = 0.01], and incidence of macrosomia [RR=0.15, 95%CI=(0.04, 0.66), Z = 2.53, P = 0.01] in the intervention group consisting of GDM patients. There were no statistical differences in preterm delivery outcomes [RR=0.44, 95%CI=(0.09, 2.16), Z = 1.01, P = 0.31]. Conclusion: Resistance training can improve blood sugar levels, insulin usage, and some adverse pregnancy outcomes in patients with GDM and is therefore worthy of clinical promotion.